Onconephrology: the significance of renal function for the development, diagnosis, and treatment of cancer - Delecluse, Susanne; Harder, Fridtjof; Keller, Frieder; Zeier, Martin; Zschäbitz, Stefanie (Deutsches Ärzteblatt, 2024)
Background: Modern treatment strategies have markedly improved the chances of survival for patients with cancer. As the population ages, cancer is becoming more common, as is chronic kidney disease (CKD). CKD increases the risk of cancer; conversely, cancer treatments can cause CKD. Methods: This review is based on publications retrieved by a selective literature search concerning the epidemiology and comorbidities of cancer and kidney diseases, the renal side effects of new anticancer drugs, and the need to consider renal function in cancer treatment. Results: The prevalence of severe CKD in Germany is 2.3%. Persons who have CKD, are on dialysis, or have undergone kidney transplantation are 1.2 to 3.5 times more likely to develop cancer than the general population. For patients who have CKD or are dialysis-dependent, the doses of approximately 67% of anticancer drugs need to be adjusted on the basis of their glomerular filtration rate and the renally excreted fraction of the drug. The optimal efficacy of therapeutic drugs, as well as of those used for diagnostic purposes, and the minimization of side effects, depend critically on adapted dosing and on proper timing of administration before or after dialysis. Modern anticancer drugs can also cause acute kidney damage (incidence with checkpoint inhibitors: 2-16%). Conclusion: Patients who have CKD, are on dialysis, or have undergone kidney transplantation make up a considerable fraction of persons being treated for cancer, and they need interdisciplinary treatment.
Gesehen am 02.10.2025